X- and gamma-ray irradiation effects on vanadium pentoxide thin films. Issue 6 (3rd July 2018) - Yılmaz, Demet; Güzeldir, Betül; Akkuş, Tuba; Öznülüer, Tuba
Abstract: Thickness and composition of thin films can be measured with X- and gamma-rays. In this work, thickness and composition of vanadium pentoxide thin films are investigated by energy dispersive and wavelength dispersive X-ray fluorescence systems. Also, the surface analysis of vanadium pentoxide thin films irradiated with Rhodium Kα X-rays and 59.54 keV gamma-rays emitted from 100 mCi and 5 Ci Americium-241 radioactive sources is performed by scanning electron microscope. It is observed that X- and gamma-rays are destructive for vanadium pentoxide thin films. Also, the composition of vanadium pentoxide thin films changes by irradiation with X- and gamma-rays.